PENGARUH HARGA, KEPERCAYAAN, KEMUDAHAN, KUALITAS INFORMASI DAN KUALITAS LAYANAN TERHADAP KEPUTUSAN PEMBELIAN SECARA ONLINE PADA SITUS ZALORA (STUDI PADA MAHASISWA KOS PERUMAHAN GRIYA SHANTA EKSEKUTIF MALANG) - Rifma Azizatun Novianti; Rois Arifin; M. Hufron (UNIVERSITAS ISLAM MALANG, 2019)
AbstractThe purpose of this study was to find and analyze the impact of price, trust, convenience, information quality, and service quality on the Zalora site's online purchasing decision for Griya Shanta Eksekutif Housing Malang students.The sample for this study was 85 students who participated in the Zalora site, and data collection was done by distributing questionnaires. Analysis of the data used in this study used instrument tests, normality tests, multiple regression analysis, classic hypothesis tests, and hypothesis tests.The results showed that the price variable has a sig value of 0,000 <0,05, that the price has a significant effect on purchasing decisions. The trust variable has a sig value of 0.004 <0.05, that trust has a significant effect on purchasing decisions. Convenience variables have a sig value of 0.001> 0.05, that ease has a significant effect on purchasing decisions. Information quality variables have a sig value of 0,000 <0,05, that the quality of information has a significant effect on purchasing decisions. Service quality variables have a sig value of 0.001 <0.05, that service quality has a significant effect on purchasing decisions.Keywords: price, trust, convenience, information quality, service quality